STAYING SOCIAL: SOCIOEMOTIONAL CONNECTIONS AND MEANING-MAKING. (11th November 2018) - Raue, M; Miller, J; Ward, C; Brady, S; D'Ambrosio, L; Ellis, D; Felts, A; Coughlin, J F
Abstract: This presentation will discuss the role of social connections, activities and rituals in creating meaning for older adults throughout the lifespan and in times of transition. The MIT AgeLab Lifestyle Leaders are a well-educated and active group that knows how to combat loneliness by being actively involved in the community and finding activities and peers with whom to socialize. Researchers will present findings from three panel studies related to romantic relationships and friendships among the Lifestyle Leaders as well as different activities that bring meaning, structure and a sense of identity to their lives. Communication technologies are indispensable to them as ways to remain connected to their loved ones. Learning and helping others was among the most mentioned current sources of meaning and purpose, while "doing what you love" grew as a prioritized source of meaning as participants have aged.